Access to Micro credit and its Impact on Farm Profit among Rural Farmers in Dryland of Sudan - Abdelateif Hassan Ibrahim; Siegfried Bauer (Global Journal of Plant and Soil Sciences, 2023)
Despite the efforts that have been made by government and NGOs to provide credit for rural farmers, yet credit is lacking where it is most needed. This study is primarily intended to assess the access to credit problem that persists in dryland of Sudan, taking North Kordofan as case in point. In addition, it tries to sort-out factors influencing the profit of farmers from agriculture. The study relies on filed survey that is conducted in 2009, using structured questionnaire. It surveyed 200 farm households, which were selected through a multi-stage random sampling technique. Descriptive statistical analysis and Heckman model were applied to analyze the data. Results showed that, farm profits for all categories were SDG 920 (100 SDG ≈ 18 €). The credit users were found to be better off with a profit of SDG 955 compared to SDG 882 for credit non-users. Results obtained from a probit model showed that savings, value of assets and incomes are significant variables determining the credit constrained conditions. In addition, the results of Heckman model showed that credit has limited effect on farm profits. This indicates that loan volumes may be too small for making a significant impact on farm production. Knowing the fact that using OLS for testing the parameters produces a bias in sample, the study used the Heckman model to correct the expected biases. The study suggests that in order for the farm profits to be improved, the agricultural investment should be improved, particularly the adoption of efficient and sustainable technology. This could be possible through increasing the loan amount with faultless repayment records.